Primary renal synovial sarcoma: computed tomography imaging findings. (April 2015) - Lv, Xiao-Fei; Qiu, Ying-Wei; Han, Lu-Jun; Cao, Jing; Zhang, Chao; Liu, Zhen-Yin; Zhang, Xue-Lin; Cai, Pei-Qiang; Li, Li
Background: A synovial sarcoma arising from the kidney is extremely rare. To date, few data are available on their radiological features. Purpose: To identify the computer tomography (CT) imaging findings of primary renal synovial sarcomas (PRSSs). Material and Methods: Five cases of PRSS confirmed by histopathological and cytogenetic studies were retrospectively analyzed. All patients had undergone unenhanced and multiphase enhanced CT examinations (one patient underwent CT twice). The CT characteristics, including shape, size, margin, attenuation, and enhancement pattern after intravenous contrast medium injection, were analyzed. Results: The study involved two female and three male patients (mean age, 27.4 years; range, 15–43 years). Unenhanced CT showed completely or partly well-defined masses, with heterogeneous ( n  = 5) or homogeneous ( n  = 1) patchy low density. On multiphase contrast-enhanced CT, in five of the six CT examinations, the tumors appeared as solid-cystic masses with cyst walls or pseudo-capsules, and demonstrated moderately heterogeneous ( n  = 5) and/or septate enhancement ( n  = 2), with a "rapid wash-in and slow wash-out" pattern of enhancement in the solid component. Only one tumor showed a simple cyst appearance and developed an irregular, intratumoral, septate soft density 8 months later. A renal vein and inferior vena cava thrombus was noticed in one patient, while lymphadenopathy was not observed in any patient. Conclusion: PRSS should be included in the differential diagnosis when an adolescent or young adult presents with a renal neoplasm appearing as a solid-cystic mass with well-defined borders, a cystic wall or pseudo-capsule, heterogeneous or septate enhancement, a "rapid wash-in and slow wash-out" pattern of enhancement in the solid component, and no sign of lymphadenopathy.